Exposure to Community-Based Violence on Social Media among Black Male Emerging Adults Involved with the Criminal Justice System. (23rd May 2020) - Motley, Robert O; Chen, Yu-Chih; Johnson, Carnayla; Joe, Sean
Abstract: The prevalence of community-based violence (CBV) exposure among black American male emerging adults ages 18 to 25 with a history of involvement with the criminal justice system is a major public health concern. Although exposure (whether as victim or witness) to CBV is linked with negative outcomes, empirical research examining black men's negative emotional responses to seeing videos of real-life incidents of CBV on social media is scant. To address these identified concerns and make recommendations for future research, the present study examines the relationship between seeing videos of CBV on social media and three types of negative emotional responses (that is, feeling sad, angry, and fearful) prior to incarceration among a sample of 101 black men detained in a midwestern jail. Social media use and seeing videos of CBV on social media were moderately high for study participants. Seeing a video involving police violence was significantly associated with an increase in the odds of feeling sad, angry, and fearful. Social media research is an emerging area that has the potential to advance our understanding of the impact of seeing social media videos of police violence on the well-being of black men and factors that mediate or moderate this relationship.